Analysis Of The Influence Of Price And Location On Tourists' Revisit Intention At Faunaland Ancol Jakarta - Ronald Roberto; Feronika Berutu (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
The research conducted by the author aims to examine the influence of two variables, namely X1 (Price) and X2 (Location) on Y (Revisit Intention) of tourists at Faunaland Ancol using a quantitative method. Faunaland Ancol is one of the family tourist destinations located in the Taman Impian Jaya Ancol area, North Jakarta, DKI Jakarta.In the study conducted using a quantitative descriptive method, the research data collected using a questionnaire distributed directly to 100 respondents of Faunaland Ancol visitors. The analysis method used is multiple linear regression test which aims to test the relationship between independent variables (Price and location) on the dependent variable (Return Interest). The results of the analysis obtained show that the independent variables (Price and Location) have a significant influence on the dependent variable (Revisit Intention) of tourists at Faunaland Ancol. The test used is the R Square Determination Coefficient or R² of 0.563 or 56.3%. Based on this, it can be interpreted that the influence of variables X1 (Price) and X2 (Location) on variable Y (Revisit Intention) is 0.563 or 56.3% and there is a remainder of 43.7% which is influenced by other factors that are not examined in this study.